Strong fish assemblage patterns persist over sixteen years in a warming marine park, even with tropical shifts. (April 2019) - Malcolm, Hamish A.; Ferrari, Renata
Abstract: Spatial conservation plans representing existing patterns of biodiversity in Marine Protected Areas (MPAs) should be robust to changes over 10 to 20 years, a temporal scale over which MPA plans are often retained. Using data from MPAs where changes have been detected due to ocean warming, can help inform discussion on how to increase temporal robustness in planning. Our aim was to determine how well fish assemblage patterns, used to develop a Habitat Classification System (HCS) as a coarse biodiversity surrogate in MPA planning, persisted over a 16 year timeframe in a warming region (east coast subtropics) of Australia. We analysed persistence/change in fish assemblage patterns in the Solitary Islands Marine Park (SIMP) where species shifts and habitat changes associated with ocean warming have been detected. Fish relative abundance was recorded at 12 sites over 16 years (2001–2017) using roving timed counts. Strong cross-shelf patterns were maintained over that 16 year period, which included some large-scale disturbances (destructive storms, 2016 mass coral bleaching event). Overall persistence in these broad assemblage patterns suggest a well-designed HCS can be a robust tool for coarsely representing biodiversity patterns in a warming world at decadal scales. 'Tropicalisation' was detected in some categories, suggesting additional planning strategies are needed within those and beyond decadal plans. Graphical abstract: Unlabelled Image Highlights: Strong but coarse cross-shelf fish assemblage patterns persisted over 16 years This supports continued use of a habitat classification system (HCS) for spatially planning biodiversity representation Finer-scale 'tropicalisation' changes in some HCS categories require additional complimentary planning strategies